2013
DOI: 10.1051/parasite/2013011
|View full text |Cite
|
Sign up to set email alerts
|

First isolation and genetic characterization of aToxoplasma gondiistrain from a symptomatic human case of congenital toxoplasmosis in Romania

Abstract: Very limited data exists on the genetic diversity of Toxoplasma gondii from Eastern Europe. We present the first Romanian case of symptomatic congenital toxoplasmosis in which the T. gondii strain was isolated after inoculation in mice of a cerebrospinal fluid sample from a living neonate. The T. gondii strain was genotyped with 15 microsatellite markers distributed on 10 of the 14 chromosomes of T. gondii. The strain had a type II genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…New information regarding the T. gondii strains present in backyard pigs in Romania are provided, which also helps complete the scarce data regarding T. gondii genotypic diversity in eastern Europe. To date, in Romania, previous studies have shown the presence of type II isolates obtained from humans [46] and goat-kids [21]. Further studies are required to develop a more complete picture of the T. gondii genotypes present in various species of domestic and wild animals in Romania.…”
Section: Discussionmentioning
confidence: 99%
“…New information regarding the T. gondii strains present in backyard pigs in Romania are provided, which also helps complete the scarce data regarding T. gondii genotypic diversity in eastern Europe. To date, in Romania, previous studies have shown the presence of type II isolates obtained from humans [46] and goat-kids [21]. Further studies are required to develop a more complete picture of the T. gondii genotypes present in various species of domestic and wild animals in Romania.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to T. gondii were found in 104 (51·4%) of 202 domestic dogs by Elias (1966), and in 14 (25·0%) of 56 of stray dogs from Cluj-Napoca by Cozma et al (2007) using 1:100 serum dilution in the IFAT. Elias (1966) found dye test antibodies in 834 (45·3%) of 1840 rabbits, 21 (26·2%) of 80 hamsters and 3 (10·3%) of 29 rats.…”
Section: Miscellaneous Animalsmentioning
confidence: 99%
“…Recently, Costache et al . (2013) isolated viable T. gondii from the cerebrospinal fluid (CSF) of a 32-week gestational age girl born prematurely but naturally to a mother who had serological evidence of recently acquired T. gondii infection during pregnancy (the mother seroconverted between 2 and 6 months of gestation). The girl had gross evidence of hydrocephalus and microphthalmia of the left eye.…”
Section: Toxoplasmosis In Humansmentioning
confidence: 99%
“…Toxoplasma gondii is an important protozoan parasite found worldwide that potentially infects all warm-blooded vertebrates, including mammals, birds, and humans [9, 19, 39]. Sheep are an important intermediate host of T. gondii [36].…”
Section: Introductionmentioning
confidence: 99%